2004
DOI: 10.1021/nl048547p
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytic Growth of Au Nanoparticles:  From Mechanistic Aspects to Biosensors Design

Abstract: The H(2)O(2)-mediated enlargement of Au nanoparticles (NPs) and the growth mechanism are described. In addition to the deposition of gold on the NP faces, the formation of nanocrystalline clusters at the intersection of the faces is observed. The detachment of the latter nanoclusters provides additional seeds for the deposition of gold. The biocatalyzed generation of H(2)O(2) in the presence of O(2)/glucose and glucose oxidase enabled the development of an optical biosensor for glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
278
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 381 publications
(290 citation statements)
references
References 22 publications
11
278
1
Order By: Relevance
“…As expected, no such microstructure was observed in the absence of the enzyme (Fig. 1B) 16 The formation of the helical Au patterning was also conrmed using the energy-dispersive X-ray (EDX) elemental mapping measurements shown in Fig. 2.…”
supporting
confidence: 64%
See 2 more Smart Citations
“…As expected, no such microstructure was observed in the absence of the enzyme (Fig. 1B) 16 The formation of the helical Au patterning was also conrmed using the energy-dispersive X-ray (EDX) elemental mapping measurements shown in Fig. 2.…”
supporting
confidence: 64%
“…However, patterning of three-dimensional structures with high topological complexity of a helix represents a major fabrication challenge even with advanced lithographic techniques such as DPN. [16][17][18][19] Recent advances in nanomotors have facilitated the realization of the new nanomotor-based direct biocatalytic patterning method.These include the ability to navigate the motors along predetermined complex paths, to control and regulate their speed, to functionalize them with different biological or chemical entities, and to move them rapidly over large areas. 20,21 Previous studies reported that HRP-functionalized catalytic nanowire motors can be used for writing localized polymeric lines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2D). The detection limit was calculated to be 0.1 μM (3σ rule), which is two orders of magnitude lower than other GNRs-based glucose sensors (Liu et al, 2013;Saa et al, 2014) and is almost the lowest among nanoparticle-based glucose sensors (Table S1, Supplementary Information) (Bi et al, 2015;Bo et al, 2013;Jiang et al, 2010;Kong et al, 2014;Luo et al, 2015;Radhakumary and Sreenivasan, 2011;Shen and Xia, 2014;Shiang et al, 2009;Su et al, 2012Su et al, , 2015bXia et al, 2013;Yi et al, 2013;Zayats et al, 2005;Zhao et al, 2015;Zheng et al, 2015). In addition, the small error bar of the data indicates the method has very high stability (Fig.…”
Section: Z Zhang Et Almentioning
confidence: 92%
“…With the growth reaction went on wheels, the AuNP seeds were quickly grown after dropping the growth solution onto the working zone, which was driven by the selfcatalytic reduction mechanism of AuNP growth. [19] After 10 min of growth, a thick rod-like Au NPs conductive layer was prepared successfully. And each single fiber of the paper in the working zone owns full covering ofrod-like Au NPs ( Figure 1B).…”
Section: Characterization Of the Modified M-pads And The Fabrication mentioning
confidence: 99%